Low‐Cost, High‐Efficiency, and Efficiency Predictable Small Molecule Organic Dyes with Bis(4‐styryl)phenyl Amino Donor for Dye‐Sensitized Solar Cells (Solar RRL 6∕2019). Issue 6 (11th June 2019) - Ying, Xintong; Liu, Yifei; Ling, Li; Xu, Mengchen; Bao, Benzhou; Bao, Xin; Pang, Aiying; Shao, Guang; Zhang, Yingjun; Fang, Jing‐Kun
Abstract : In article no.1900066, Aiying Pang, Guang Shao, Yingjun Zhang, Jing‐Kun Fang, and co‐workers report three small molecule organic dyes (SMODs). For these SMODs, a linear correlation between the dipole moments (μ) and power conversion efficiency (η) are observed to be η = 0.817μ − 0.370 with R 2 = 0.999. This allows for a facile way to predict the power conversion efficiency of dyes with similar molecular structure.